Sistem Informasi Pengelolaan Data Ternak (Skala Usaha Mikro) Di Dinas Pertanian Dan Pangan Kabupaten Kudus Berbasis Web - Fadlilatur Rosyidah; Fajar Nugraha; Putri Kurnia Handayani (Journal of Computer and Information Systems Ampera, 2022)
At the Departement of Agriculture and Food, Kudus Regency, in the process of managing livestock data, they still use conventional methods. In the data collection process, Microsoft still uses Microsoft Excel which is still less effective and efficient. Previously, the community could not know the livestock data collection, the development of livestock in the Kudus Regency so it could not be monitored. In the livestock business data collection process, livestock development still uses livestock development records which can cause misinformation in activities and can resultin piles of livestock development data files so that they are less effective in managing livestock data because they have to work twice in the data management process at the Agriculture and Food Service Kudus District. For this reason, the research on making this information system aims to produce a system that can be used to manage livestock data (micro-scale) both commodity data, micro-scale data, livestock data collection, evidence of data collection, livestock development, counseling schedules, and reports. So it is necessary in this study to produce an Information System for animal Data Management (Micro Business Scale) at the Departement of Agriculture and Food, Kudus Regency. Keywords: Management, Animal Data, Micro Business Scale, Information Systems.